Pengaruh Perputaran Modal Kerja, Perputaran Kas dan Jumlah Kredit Bermasalah Terhadap Profitabilitas Pada KSP Madani - Gagat Riyanti; Irianto; Topan Siswanto (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to examine the influence of Working Capital Turnover, Cash Turnover and Number of Non-Performing Loans on Profitability at KSP Madani NTB for the 2018-2022 period. The financial ratios used to measure this influence are WCTO, Cash Turnover and NPL. This type of research is associative and the sampling technique used is a saturated sampling technique. The samples used for KSP Madani NTB's financial reports are the balance sheet, SHU and cash flow reports. Data was obtained through financial reports at KSP Madani NTB for the 2018-2022 period. The analytical method used is multiple linear regression analysis. The results of the multiple linear regression analysis are Y = 52.507 + 0.948X1 – 0.019X2 + 0.042X3. Partially, the variables Working Capital Turnover (WCTO), Cash Turnover and Number of Non-Performing Loans (NPL) have a significant effect on Profitability. Simultaneously the variables Working Capital Turnover (WCTO), cash turnover (Cash Turnover), and the number of non-performing loans (NPL) have a significant effect on profitability with a significance of 0.040 <0.05 indicating a significant effect on profitability. The ability of the independent variable to explain the dependent variable is 99.60% and the remaining 0.04% is influenced by other variables outside the research variables used.